Characteristics of patients with suspected COVID-19 pneumonia and repeatedly negative RT-PCR. Issue 12 (13th December 2021) - Navarro-Carrera, Paula; Roces-Álvarez, Patricia; Ramos-Ramos, Juan Carlos; Montero, Dolores; Losantos, Itsaso; Díaz-Pollán, Beatriz; García Bujalance, Silvia
Abstract : Objectives. Challenges remain and there are still a sufficient number of cases with epidemiological, clinical features and radiological data suggestive of COVID-19 pneumonia that persist negative in their RT-PCR results. The aim of the study was to define the distinguishing characteristics between patients developing a serological response to SARS-CoV-2 and those who did not. Methods. RT-PCR tests used were TaqPath 2019-nCoV Assay Kit v1 (ORF-1ab, N and S genes) from Thermo Fisher Diagnostics and SARS-COV-2 Kit (N and E genes) from Vircell. Serological response was tested using the rapid SARS-CoV2 IgG/IgM Test Cassette from T and D Diagnostics Canada and CMC Medical Devices and Drugs, S.L, CE. Results. In this cross-sectional study, we included a cohort of 52 patients recruited from 31 March 2020 to 23 April 2020. Patients with positive serology had an older average age (73.29) compared to those who were negative (54.82) ( P <0.05). Sat02 in 27 of 34 patients with positive serology were below 94% ( P <0.05). There was a frequency of 1.5% negative SARS-CoV-2 RT-PCRs during the study period concurring with 36.7% of positivity. Conclusions. Clinical features and other biomarkers in a context of a positive serology can be considered crucial for diagnosis.